Influx of refugees: Integration as a key challenge - Jochen Andritzky; Bodo Aretz; Désirée I. Christofzik; Christoph M. Schmidt (Sachverständigenrat zur Begutachtung der Gesamtwirtschaftlichen Entwicklung, 2016)
In 2015 and 2016, more than one million refugees arrived in Germany. While granting these migrants access to the country is an expression of humanitarian responsibility, their subsequent integration into the labor market is primarily a challenge for economic policy. For a wide range of outcomes, from unemployment to the stability of social security systems, successful labour market integration holds the key to reducing long run costs from the refugee influx. This paper outlines the implications for the provision of education and training, as well as for labour market and housing policy. They comprise a sustained effort to enhance the qualifications and skills of recognised asylum applicants, reforms geared to incentivising residential construction, and measures to improve labour market flexibility and (self-)employment opportunities.
Keywords: 330